STUDI LITERATUR REVIEW : PENGARUH SANITASI AIR BERSIH TERHADAPKEJADIAN STUNTING PADA BALITA - Silvia Herdinda (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
This research is motivated by the many stunting incidents experienced by toddlers due to clean water sanitation. Clean water sources are one of the causes of stunting because water is the most important part of survival. Stunting is a nutritional problem with poor development causing a lack of height in children at a certain age. This research to determine the effect of clean water sanitation on the incidence of stunting in toddlers. This research uses the literature review method, which is a search for national literature taken or found in several journals, articles and research studies that aim to identify, evaluate, and summarize all quality and relevant findings. Based on the title search, 16 journal articles were found that met the criteria. The results showedthat there was an effect of clean water sanitation on the incidence of stunting in toddlers. There is criteria for causing stunting in toddler like influlence of WASH (Water, Sanitation, And Hygiene). So that clean water affects the occurrence of stunting. Stunting must be minimized immediately so that it does not increase every year.